(untitled) (Herald of the National Children’s Medical Center, 2025)
Aim. To improve the outcomes of surgical treatment by developing new diagnostic approaches and introducing minimally invasive organ-preserving interventions in children with congenital lung malformations (CLM). Materials and Methods. The study is based on the results of examination and treatment of 146 pediatric patients with CLM, aged from birth to 18 years, who underwent inpatient treatment between 2004 and 2024 at the clinics of TashPMI and the National Children’s Medical Center (NCMC). Clinical and instrumental methods were applied (X-ray, MSCT, bronchoscopy, echocardiography, angiography), bronchography to determine the volume of surgery, intraoperative visual assessment, and surgical treatment including resections and bronchial sealing with biopolymer. Results. Surgical treatment of CLM in children (VATS lobectomy and bronchial sealing) yielded positive outcomes in 92.7% of patients. VATS lobectomy and sealing provided better functional results and fewer complications, with preserved ventilatory capacity. Conclusion. Comprehensive diagnostics is essential for evaluating CLM. VATS lobectomy and bronchial sealing, as organ-preserving methods, are effective, reduce surgical trauma, hospitalization time, and the risk of disability.